2016
DOI: 10.5935/0004-2749.20160046
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting visual acuity after accelerated crosslinking in patients with progressive keratoconus

Abstract: Purpose: The present study aimed to report the outcomes of patients with progressive keratoconus who were treated via accelerated crosslinking (CXL) 6 months earlier and to determine the factors that promoted improved visual acuity after treatment. Methods: This retrospective study included 35 eyes of 34 patients with progres sive keratoconus who underwent CXL. Topographical measurements were obtained preoperatively and in the first, third, and sixth months postoperatively using a rotating Scheimpflug camera. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
5
8
0
Order By: Relevance
“…The mean average K decreased in group I & II by (0.216±0.633 and 0.250± 1.665) respectively p=0.261 and 0.619 respectively. These findings were in parallel to those of Ahmet Kırgız et al's study [11] and Paolo Vinciguerra et al's study [12] who showed decrease in the mean average K by (0.13D), (2.74D) respectively p=(0.240) and (<0.05) respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The mean average K decreased in group I & II by (0.216±0.633 and 0.250± 1.665) respectively p=0.261 and 0.619 respectively. These findings were in parallel to those of Ahmet Kırgız et al's study [11] and Paolo Vinciguerra et al's study [12] who showed decrease in the mean average K by (0.13D), (2.74D) respectively p=(0.240) and (<0.05) respectively.…”
Section: Discussionsupporting
confidence: 89%
“…In the B.ele.Th value, an increase was determined of 1.61µm in the Kmax 0-1 D steepening group and 2.75µm in the >2 D flattening group (Table 3), (Table 4). There have been reports of increased posterior elevation after CXL (21,22). It is suggested that posterior steepening together with anterior flattening may be the cause for the stabilization of keratometric values after CXL (22).…”
Section: Discussionmentioning
confidence: 99%
“…5 Many studies showed the efficacy of CXL not only in ceasing the progression of keratectasia, but also in flattening the cornea. [6][7][8][9][10][11] While corneal flattening resulted in an improved visual acuity in mild to moderate disease, 12,13 no change in visual function was reported in advanced keratoconus but rather stromal opacities in some cases of thin cornea. [14][15][16] Also, corneal flattening after CXL was correlated with advanced keratoconus, characterized by high preoperative keratometry (above 54.00 D) and thin pachymetry.…”
Section: Introductionmentioning
confidence: 99%